A micro-based approach to evaluate the effect of water supply on health in Uganda. (September 2021) - Frempong, Raymond Boadi; Kitzmüller, Lucas; Stadelmann, David
Highlights: We merge individual panel datasets with sub-county level administrative data on water supply projects. We estimate fixed-effects panel regressions to account for spatial and temporal variation at the sub-county level. Provision for improved water is found to have a significant effect on water usage and water collection times. No statistically significant effects of improved water are found for reported diarrhoea incidence. Our approach is a cost-effective means of evaluating development projects. Abstract: This paper proposes a micro-based approach to investigate the impact of improved water provision on individual health outcomes in rural Uganda. We merge household and individual panel datasets with sub-county level administrative data on water supply projects. Our approach allows us to estimate fixed-effect panel data models which use temporal and spatial variation at the sub-county level as identifying variation. We find evidence that the installation of improved water sources leads to higher reported improved water usage, and shorter water collection times. However, increasing the sub-county rate of improved water sources per capita does not seem to be sufficient to lead to a statistically significant effect in the likelihood of individuals suffering from symptoms of illness associated with inadequate water supply. We argue that our micro-based approach provides a cost-effective means of evaluating development projects. The approach is scalable, i.e. it can be applied to other settings and countries.